Antioxidative activities of phenolic compounds isolated from Inonotus obliquus - Kim, H.J.; Jin, C.; Lee, Y.S. (2007)
In our continued search for biologically active compounds from traditional medicine, we found that ethyl acetate fraction from Inonotus obliquus showed potent antioxidant activities on three different cell-free bioassay systems. Bioassaydirected chromatographic fractionation of the ethyl acetate fraction from Inonotus obliquus afforded four phenolic compounds, 4-(3,4-dihydroxyphenyl) -(？)-3-buten-2-one (1), 3,4-dihydroxybenzaldehyde (2), protocatechuic acid (3) and caffeic acid (4) along with three sterols such as lanosterol (5), ergosterol peroxide (6) and 9,11-dehydroergosterol peroxide (7). Among isolates, phenolic compounds (1-4) were assessed for antioxidant activities. Almost phenolic compounds showed potent DPPH and superoxide anion radicals scavenging and lipid peroxidation inhibitory activities indicating that these phenolic compounds contribute to the antioxidative activities of /. obliquus. Compounds 2-3 and 7 were isolated for the first time from this plant.